Insulin Modulates Inflammatory Cytokine Release in Acute Stages and Augments Expression of Adhesion Molecules and Leukocytes in Lungs on Chronic Stages of Paracoccidioidomycosis - Casagrande, Felipe Beccaria; Ferreira, Sabrina de Souza; de Sousa, Emanuella Sarmento Alho; Guimarães, João Pedro Tôrres; Romera, Lavínia Maria Dal’Mas; Tessaro, Fernando Henrique Galvão; Almeida, Sandro Rogério de; Rodrigues, Stephen Fernandes de Paula; Martins, Joilson O. (Frontiers in Immunology, 2020)
Type 1 diabetes mellitus is caused by partial destruction of insulin-producing beta cells from the pancreas, and is a major issue for public health care worldwide. Reduced or impaired immunological responses, rendering patients more susceptible to infections, have been observed on T1D, often related this dysfunction to the lack of insulin in blood. Paracoccidioidomycosis is an important systemic mycosis endemic in whole Latin America. In order to evaluate the effects of T1D on this fungal infection, and furthermore the modulatory effects of insulin in it, we used C57Bl/6 male mice rendered diabetic (alloxan 60mg/kg), infected (Pb18, 1 x 106 cells) and treated with NPH insulin (2IU/600mg/dL of blood glucose). 24 hours after infection, infected diabetic mice shower reduced secretions of IFN-γ and IL-12 p70 compared to non-diabetic infected controls. On the 45th day of infection, diabetic infected mice presented higher levels of IFN-γ, higher TNF-α:IL-10 ratio, and reduced expression of adhesion molecules compared to non-diabetic. In in vitro experiments, alveolar macrophages from diabetic animals showed reduced phagocytic activity compared to controls in 4h, 12h and 24h interactions. Treatment with insulin in diabetic infected mice restored IL-12 p70 in 24h of infection, reduced levels of IFN-γ, and TNF-α:IL-10 ratio in 45 days and restored VCAM-1 expression in pulmonary blood vessels, while reducing in diminished phosphorylarion of ERK MAPK and showing higher levels of iκb-α and JNK p46 in non-diabetic infected mice. In addition, insulin promoted higher phagocytic activity in alveolar macrophages of diabetic mice. This data suggests T1D mice are more susceptible to Pb18 infection, and insulin modulates this inflammation in diabetic mice, augmenting expression of adhesion molecules and leukocytes in lungs, and reducing chronic inflammation.